The Impact of Unresolved Grief in Children on Sleep Disorders with the Mediating Role of Cognitive Emotion Regulation and Rumination in Adolescents - Yosefvand, Narjes; Rahmani, Marjan; Vafapor, Parisa (Mental Health and Lifestyle Journal, 2024)
This study aimed to investigate the impact of unresolved grief in children on sleep disorders in adolescents, with cognitive emotion regulation and rumination examined as mediating variables. A descriptive correlational design was employed, involving 363 adolescents aged 13 to 18 years from Tehran. Participants were selected using stratified random sampling based on the Morgan and Krejcie sample size table. Standardized self-report questionnaires were used to measure unresolved grief, cognitive emotion regulation, rumination, and sleep disorders. Data analysis was performed using SPSS-27 for Pearson correlation and AMOS-21 for structural equation modeling (SEM). Model fit indices and path coefficients were calculated to examine both direct and indirect effects. The results revealed that unresolved grief had a significant direct effect on sleep disorders (β = 0.28, p < .001) and also influenced sleep through cognitive emotion regulation (β = 0.10, p = .004) and rumination (β = 0.15, p < .001). Cognitive emotion regulation positively predicted rumination (β = 0.52, p < .001), and both mediators significantly predicted sleep disorder (β = 0.24 and β = 0.33, respectively). The total effect of unresolved grief on sleep disorder was substantial (β = 0.48, p < .001). The model demonstrated a good fit to the data (χ²/df = 2.32, CFI = 0.96, RMSEA = 0.058, TLI = 0.95). The findings highlight the critical role of cognitive and ruminative mechanisms in linking unresolved grief to sleep disturbances in adolescents. Early intervention targeting emotion regulation strategies and rumination may mitigate the adverse psychological and physiological consequences of childhood grief and improve adolescent sleep health.